Neurodevelopmental outcomes of very preterm and very-low-birthweight infants in a population-based clinical cohort with a definite perinatal treatment policy. (September 2020) - Pascal, Aurelie; Naulaers, Gunnar; Ortibus, Els; Oostra, Ann; De Coen, Kris; Michel, Sonnaert; Cloet, Eva; Casaer, Alexandra; D'haese, James; Laroche, Sabrina; Jonckheere, An; Plaskie, Katleen; et al.
Abstract: Background: With constant changes in neonatal care practices, recent information is valuable for healthcare providers and for parental counselling. The aim of the study was to describe the neurodevelopmental outcome in a cohort of very preterm (VPT)/very-low-birthweight (VLBW) infants at 2 years corrected age (CA). Material and methods: This is a population-based cohort study of all infants born with a GA <31 weeks and/or BW < 1500 g between 2014 and 2016 admitted to the Flemish (Belgium) neonatal intensive care units. Infants had routine clinical follow-up around 2 years CA. The diagnosis of cerebral palsy (CP), visual and hearing impairments were recorded. Motor, cognitive and language outcomes were assessed using the Bayley-III. Neurodevelopmental impairment (NDI) was classified as mild (<1 standard deviation [SD]) or moderate-severe (<2SD) based on the defined categories of motor, cognitive, hearing, and vision impairments. Results: Of the 1941 admissions, 92% survived to discharge and follow-up data were available for 1089 infants (61.1%). Overall, 19.3%, 18.9% and 41.8% of infants had a motor, cognitive and language delay, respectively. CP was diagnosed in 4.3% of the infants. Mild and moderate-to-severe NDI was observed in 25.2% and 10.9% of the infants, respectively. The number of infants with a normal outcome increased from nearly 40% in the category of GA<26 weeks to 70% for infants in the category of 30─31 weeks GA. Conclusion: At 2 years CA, 64% were free from NDI and 90% were free from moderate-to-severe NDI. However, a lower GA and BW are associated with higher rates of adverse neurodevelopmental outcomes at 2 years CA. Highlights: 92% of the VPT/VLBW infants survived to discharge. At 2 years corrected age, 64% were free from neurodevelopmental impairment. At GA <26 weeks, 69% survived and 60% had adverse neurodevelopmental outcome.